Analisis Kapasitas Antioksidan dan IC 50 pada Produk Minuman Fermentasi Sari Buah Salak Bali (Salacca zalacca var. Amboinensis) Asal Desa Rendang - Widnyani, Ida Ayu Putu Ary; Yoga, Wahyu Krisna; Fitriani, Pande P Elza; Sintyadewi, Putu Rima (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2024)
Bali snake fruit (Salacca zalaca Var. Amboinensis) is an Indonesian agricultural product that can be found scattered throughout the archipelago. Utilization of snake fruit by applying process engineering with the fermentation method can provide added value and provide health benefits for the community. This study aims to determine the antioxidant capacity and free radical inhibitory activity (IC50) of the product. The samples were tested for their antioxidant capacity and antioxidant activity. The data obtained were statistically analyzed using a non-factorial completely randomized design. The study used 7 treatments and 3 replications to obtain 21 experimental units. The results showed that the treatment of differences in fermentation time on probiotic drink products of salak fruit juice had antioxidant capacity ranging from 376.552 to 761.693 mg GAE/100g. The antioxidant activity (IC 50) produced was 182.294-130.965 ppm.